Faktor-Faktor yang Mempengaruhi Underweight pada Remaja SMA di Bekasi: Factors Affecting Underweight in High School Adolescents in Bekasi - Dewie Anatasya Karno; Fitriani, Anna; Iswahyudi (JURNAL GIZI DAN KESEHATAN, 2024)
Underweight in adolescents has an impact on physical, mental, intellectual, and social health conditions. Other impacts include disruption of learning and cognitive abilities, as well as decreased concentration. Underweight is one of the multiple nutritional problems that occurs in Indonesia where there is an imbalance between nutritional intake and recommended needs. The prevalence of underweight among adolescents aged 16–18 years in Bekasi is 14.25% combined in the very thin and thin categories. The prevalence of underweight in Bekasi is quite high because it is above the national prevalence, so further research is needed regarding the factors that cause underweight in this area. This study aims to analyze the relationship between energy intake, macronutrients, nutritional knowledge, body image, and other factors (number of family members, family income) on the incidence of underweight in high school teenagers in Bekasi. This research is a quantitative research with a cross sectional study design. Data was collected from 103 teenagers obtained using simple random sampling techniques. Data on energy and macronutrient intake were obtained through interviews, data on nutritional knowledge, body image, number of family members and family income were obtained using a questionnaire. Meanwhile, underweight data was obtained using anthropometric measurements. Research data was analyzed using a two proportion difference test. Underweight among adolescents in Bekasi is significantly related to energy intake, macronutrients (protein, fat, carbohydrates), nutritional knowledge, and body image towards underweight. However, the number of family members and family income are not significantly related to underweight among high school teenagers in Bekasi. The researcher's advice is that it is hoped that students with poor nutritional status will improve their nutritional status with a healthy diet according to the recommendations for balanced nutrition.   ABSTRAK Underweight pada remaja memiliki dampak terhadap kondisi kesehatan fisik, mental, intelektual, dan sosial. Dampak lainnya yaitu terganggunya kemampuan belajar dan kognitif, serta menurunnya konsentrasi. Underweight merupakan salah satu masalah gizi ganda yang terjadi di Indonesia di mana terdapat ketidakseimbangan antara asupan zat gizi dengan kebutuhan yang telah dianjurkan. Prevalensi underweight pada remaja usia 16–18 tahun di Bekasi sebesar 14,25% gabungan kategori sangat kurus dan kurus. Prevalensi underweight di Bekasi tergolong cukup tinggi karena di atas prevalensi Nasional, sehingga perlu diteliti lebih lanjut mengenai faktor penyebab underweight di wilayah ini. Penelitian ini bertujuan untuk menganalisis hubungan asupan energi, zat gizi makro, pengetahuan gizi, citra tubuh, dan faktor lainnya (jumlah anggota keluarga, pendapatan keluarga) terhadap kejadian underweight pada remaja SMA di Bekasi. Penelitian ini merupakan penelitian kuantitatif dengan desain studi cross sectional. Data dikumpulkan dari 103 remaja yang diperoleh menggunakan teknik simple random sampling. Data asupan energi dan zat gizi makro diperoleh melalui wawancara, data pengetahuan gizi, citra tubuh, jumlah anggota keluarga, dan pendapatan keluarga diperoleh menggunakan kuesioner. Sedangkan data underweight diperoleh menggunakan pengukuran antropometri. Data penelitian dianalisis menggunakan uji beda dua proporsi. Underweight pada remaja di Bekasi berhubungan signifikan dengan asupan energi, zat gizi makro (protein, lemak, karbohidrat), pengetahuan gizi, dan citra tubuh terhadap underweight. Namun, jumlah anggota keluarga dan pendapatan keluarga tidak berhubungan bermakna dengan underweight pada remaja SMA di Bekasi. Saran peneliti diharapkan siswa dengan status gizi kurang agar meningkatkan status gizi dengan pola makan sehat sesuai anjuran gizi seimbang.